Transcriptomic and metabolomic analysis reveals hepatic lipid metabolism disruption in Japanese quail under polystyrene microplastics exposure - Xinxin Zhang; Lingyang Jing; Xiaoqing Pei; Qingyu Zhang; Hongfeng Zhao (Emerging Contaminants)
Microplastics (MPs) become a global concern due to their impacts on human and wildlife health. In this study, we attempted to determine the hepatotoxic effects of MPs exposure on birds by using a laboratory model animal-Japanese quail (Coturnix japonica) through integrating transcriptomic and metabolomic analysis. Seven-day old female chicks were exposed to low concentrations (0.02 mg/kg, 0.4 mg/kg) and high concentration (8 mg/kg) polystyrene microplastics (PS-MPs) of environmental relevance in the feed for 35 days. The results showed that 0.02 mg/kg and 0.4 mg/kg PS-MPs exposure caused increasing food and water intake with weight gain and liver lipid droplets accumulation while 8 mg/kg PS-MPs exposure induced decreasing food and water intake with weight loss. Moreover, both microstructural damage and ultrastructural injury indicated liver malfunction by PS-MPs exposure. PS-MPs also led to hepatic oxidative stress. Furthermore, untargeted metabolomic analysis showed lipid metabolism disturbance in the liver of PS-MPs exposure. Transcriptomic results also showed molecular signaling pathway disruption in the liver of PS-MPs exposure. Especially, lipid metabolism including peroxisome proliferator activated receptor (PPAR) signaling pathway, fatty acid oxidation, primary bile acid synthesis and triglyceride metabolism were disrupted by PS-MPs exposure. The present study concluded MPs exposure might have hormetic effects on bird development and it posed risks to bird health with low dose MPs may induce non-alcoholic fatty liver disease while high dose MPs may cause severe histopathological injury and oxidative damage. This study underscored the importance of evaluating the chronic effects of microplastics on birds.